Correlation of Cristocentric Hermeneutics with Lexionary Sermons - Thomas Kartomo (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
Confusion among Christians about the concept of salvation by God through Jesus Christ can disrupt their faith. Therefore, churches need to develop anticipatory strategies to overcome this phenomenon, one of which is through preaching. Effective faith-building preaching should be Christocentric, focusing on Jesus as the center of teaching. To achieve this, two conditions must be met: first, a hermeneutic perspective oriented towards Jesus, since this will influence the homiletic methods used; second, biblical readings that support that focus, in which the lexionary is designed to be gospel-centered. Finding the relationship between Christocentric hermeneutics and lexionary is essential to assess the extent to which these two elements can strengthen the faith of the congregation. Biblical and field research shows that both Jesus and his disciples applied a Christocentric approach to Bible reading and teaching. Luke 24:25-27 shows that Jesus is the central figure of the preaching in the Torah, the prophets, and the Psalms. Because in Luke 24:44 Jesus emphasizes the importance of reading the Bible with a Christocentric perspective. Colossians 1:15-20 is an example that shows the connection of this perspective to the theme of God's creation and salvation. The results of the study also showed that the cristocentric perspective was valid both in the context of Christian hermeneutics and in general, with survey analysis showing a positive correlation between Christocentric hermeneutics and lexionary sermons intended for congregations.